Upaya Qismu Ri’ayah dalam Pelaksanaan Bimbingan dan Konseling Bagi Santri Pondok Pesantren - Syafiq, Mohamad; Mohammad, Salavi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
Guidance and counseling is an activity of providing assistance to other people to help them solve a problem they have. Darullughah Wadda'wah Islamic Boarding School is an Islamic educational institution that has thousands of students, To carry out supervision on each individual student is not an easy thing, then a section (qism) was formed called the supervisory section (qismu ri'ayah) which aims to carry out supervision through a